Structure Determination by X-ray Crystallography - Ladd, Mark; Palmer, Rex (Springer, 2013)
We were honoured to be asked by Springer, New York to prepare a fifth edition of Structure Determination by X-ray Crystallography. First published in 1977 under the Plenum imprint, this book has received wide acclaim in both teaching and research in X-ray crystallography because of its extensive and detailed coverage of all aspects of the subject. As we prepare this new edition, we are entering the centenary of the discovery of X-ray diffraction in 1912, the beginning of X-ray crystallography as a science in its own right. Today, X-ray crystallography and the complementary technique of neutron diffraction together provide the most powerful tools for the investigation and elucidation of crystal and molecular structures. X-ray and neutron crystallography may be described as the science of the structure of materials, in the widest sense of the phrase, and their ramifications are evident across a broad spectrum of scientific endeavour. The power of computers and available software has unleashed an unprecedented ability to carry out with speed the complicated calculations involved in crystal structure determination on a desktop PC. This is paralleled by the availability of powerful X-ray and neutron sources and low temperature devices for facilitating measurements at liquid nitrogen temperature or lower, which provide ever higher precision in the determination of crystal structures. However, a detailed knowledge of the theory underlying the process of crystal structure determination is still required in order both to ensure that the literature contains correct well-determined structures and to understand the complexities introduced by features such as disorder and twinning in crystals. There are many pitfalls in crystal structure determination to trap the unwary. In this new edition, we have continued the approach that has been well reviewed in its earlier editions. We have always kept in mind that students meeting X-ray crystallography for the first time are encountering a new discipline, and not merely extending the range of a subject already studied. In consequence, we have chosen, for example, to discuss the geometry and symmetry of crystals in rather more detail than is found in other books on this subject, for it is our experience that some of the difficulties that students meet in introductory X-ray crystallography lie in their unfamiliarity with a three dimensional concept,whether they be final-year undergraduate or post-graduate students in chemistry, biochemistry,materials science, geology, bioinformatics, information technology, or physics. Both low molecular weight (small molecules) and macromolecular methods (proteins) are covered in detail.
Analysis by X-rays and Neutrons
Keywords: X-ray Crystallography